PERFORMANCE MEASURE OF VARIOUS MACHINE LEARNING OPTIMIZERS FOR DIABETES PREDICTION IN INDIAN WOMAN. - Goura, Surendra; Nafis, Md. Tabrez; Parveena, Suraiya (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper presents a comprehensive comparative analysis of gradient descent optimization algorithms using a Diabetes Prediction dataset. The study explores their strengths, weaknesses, and performance characteristics under two different conditions, namely with and without feature engineering. The objective is to obtain proper insights into the effectiveness and efficiency of these algorithms in predicting diabetes. The analysis focuses on widely used algorithms, including stochastic gradient descent (SGD) and advanced variants like Nesterov accelerated gradient and adaptive learning rate techniques (e.g., Adam, AdaGrad, AdaMax, and AdaDelta). By evaluating their performance on the dataset under two different scenarios this research provides valuable insights into the performance of these algorithms. The obtained result show that, SGD variants (classic SGD, momentum, Nesterov), RMSProp, Adam, AdaMax, and Nadam outperformed AdaGrad and AdaDelta in minimizing error (lower MAE values) in both scenarios.